A contribute to the default-interventionist and parallel accounts in deductive reasoning. The effect of decisional styles on logic and belief. - Fabio, Rosa Angela; Verzì, Dalila; Gangemi, Amelia (Journal of General Psychology)
Classical theories of reasoning equate System 1 with biases and System 2 with correct responses. Refined theories of reasoning propose the parallel model to explain the two systems. The first purpose of the present article is to give a contribution to the debate on the parallel and default-interventionfist models: we hypothesized when logic and belief conflict both logical validity and belief judgments will be affected with greater level of response errors and/or longer response times. The second purpose of this article is to assess the relationship between decisional styles and performance in deductive reasoning. Seventy-two participants participated in the experiment and completed 64 modus ponens and modus tollens syllogistic reasoning tasks. Accordingly, we found that belief and logic judgments were affected by the conflict condition, both in easy syllogisms (i.e., modus ponens) and in complex syllogisms (i.e., modus tollens). Findings showed also that participants with a rational decision-making style were more strongly influenced by logic than belief, whereas those with an intuitive decision-making style were more strongly influenced by belief than logic.